Solvatochromism and ZINDO-IEFPCM solvation study on NHS ester activated AF514 and AF532 dyes: Evaluation of the dipole moments - Patil, Mallikarjun Kalagouda; Kotresh, Mare Goudar; Tilakraj, Tarimakki Shankar; Inamdar, Sanjeev Ramchandra (European Journal of Chemistry, 2022)
In this study, the solvatochromic effect on the photophysical properties of Alexa Fluor 514 (AF514) and Alexa Fluor 532 (AF532) fluorescent dyes is examined experimentally and computationally. To explore the solvatochromism and dipole moments, the steady-state absorption and fluorescence spectra of the dyes were measured in a series of organic solvents. Various solvent correlation models, like Bilot-Kawski, Lippert-Mataga, Bakhshiev, Kawski-Chamma-Viallet, and Reichardt microscopic solvent polarity parameters, were adapted to determine the dipole moments in their ground and excited states. For the computational investigation, the ground and excited-state geometries are optimized using density functional theory (DFT) and time-dependent density functional theory (TD-DFT), respectively, in vacuum. Furthermore, semiempirical ZINDO with the IEF-PCM model is used to evaluate the absorption transition energies of these dyes, which are comparatively studied in various solvent polarity along with experimental data. Additionally, the highest occupied molecular orbital energies (HOMO) and lowest unoccupied molecular orbital energies (LUMO), chemical softness, chemical hardness, energy gap, chemical potential, electronegativity, and molecular electrostatic potential (MEP) were estimated using DFT calculations at the CAM-B3LYP/6-311G(d,p) level, in gas phase. The experimental and computational results reveal that the singlet excited state dipole moment is greater than that of the ground state for the molecules considered. The angle between ground- and singlet excited-state dipole moments are found to be 0.50 and 0.49° making them almost parallel to each other. The natural bond orbital analysis (NBO) has been employed to investigate the stability of the molecule, inter- and intra-hyper-conjugative interactions and charge delocalization within the molecule.